2021
DOI: 10.3390/ijerph18147643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training on Cardiopulmonary Function and Quality of Life in Elderly Patients with Pulmonary Fibrosis: A Meta-Analysis

Abstract: (1) Objective: Our objective was to conduct a meta-analysis of randomized controlled trials that have evaluated the benefits of exercise training for elderly pulmonary fibrosis (PF) patients. (2) Methods: Studies in either English or Chinese were retrieved from the China National Knowledge Infrastructure (CNKI) and the Wanfang, PubMed, Web of Science and SPORTDiscus databases from inception until the first week of April 2021. Age, body mass index (BMI), and exercise frequency, intensity, type, and duration wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 85 publications
(338 reference statements)
1
7
0
Order By: Relevance
“…Several robust studies have shown the health benefits of physical activity in cardiopulmonary function, neuroplasticity, cognition, and bone density [582,583]. Interestingly, related to bone density, it was recently reported the discovery of a specialized bone-cell progenitor that supports immune cell generation in response to physical Fernández-Calle et al Molecular Neurodegeneration (2022) 17:62 exercise [584].…”
Section: Physical Exercisementioning
confidence: 99%
“…Several robust studies have shown the health benefits of physical activity in cardiopulmonary function, neuroplasticity, cognition, and bone density [582,583]. Interestingly, related to bone density, it was recently reported the discovery of a specialized bone-cell progenitor that supports immune cell generation in response to physical Fernández-Calle et al Molecular Neurodegeneration (2022) 17:62 exercise [584].…”
Section: Physical Exercisementioning
confidence: 99%
“…Apart from the widely acknowledged cardiovascular and musculoskeletal benefits of exercise in chronic disease patients, studies have described specific mechanisms of physical training to maintain respiratory function [29,30]. It was reported that a single bout of moderate-intensity exercise might have an acute bronchodilator effect, increasing both FEV1 and FEF27-75 [31].…”
Section: Discussionmentioning
confidence: 99%
“…(5) Patients who were not malnourished; (6) Patients who had an expected survival time of more than 6 months; (7) The Karnofsky performance status score was more than 60 points in patients; (8) The age of the patients was more than 18 years old; and (9) Patients who had good tolerance and compliance. In the following circumstances, patients were not included in this study: (1) Patients with some factors such as hearing impairment, language disorders, unconsciousness or mental illness, and patients who could not communicate with others; (2) Patients with a grave organic disease or dysfunction in vital organs; (3) Patients with complications, such as pulmonary infection and respiratory failure; (4) Patients with malnutrition or excessive obesity; (5) Patients with the expected survival period <6 months; and (6) Patients with the training participation rate <80%.…”
Section: General Informationmentioning
confidence: 99%
“…At present, chemotherapy has an exact effect on SCLC, and about 1% of patients can be cured by chemotherapy (6). However, the effects of chemotherapy in patients with NSCLC are unsatisfactory, and patients can only relieve the clinical symptoms through chemotherapy drugs, which cannot effectively improve pulmonary function (7). For patients with NSCLC with the EGFR gene mutation, the T790M mutation will lead to an increase in chemoresistance, and patients who are insensitive to the conventional pemetrexed often get worse after treatment (8).…”
Section: Introductionmentioning
confidence: 99%